Evolution of the oxidation of V zigzag nanostructures on Si: Prime conditions to reach uniform thermochromic VO2(M) thin films - F.M. Morales; J.J. Jiménez; N. Martin; R. Alcántara; J. Navas; R. García; A.J. Santos (Applied Surface Science Advances)
This article reports on the oxidation of 100 nm-thick vanadium layers achieved by sputtering glancing-angle deposition on silicon, with opposite oblique columns creating a zigzag-like morphology, using a small overpressure continuous flow of air and an infrared lamps furnace. In addition, the study focuses on the stepwise investigation of the nanostructure and the oxidation progress of the layer by electron microscopy, verifying a monotonic incorporation of oxygen with time, which results in a linear rise of the VOx overlayer volumes. This characterization is correlated with Raman spectra quickly collected in a wide wavenumber range. In consequence, we claim a methodology based on the comparisson of the relative intensities of such Raman bands to track the kinetic dynamics of these systems, evidencing the participation of three main phases: VO2(M) alone or mixed with either V or V2O5. For the optimum conditions, high-quality vanadium dioxide layers are achieved, attending to their nanostructure and outstanding optical response (over 90% of relative transmittance modulation at a wavelength of 3000 nm). Vis-NIR spectrophotometry and Raman spectroscopy, both carried out at variable temperature, allow exploring the different thermochromic characteristics of the samples at different oxidation stages.